Farmers’ requirements for sorghum seed products in Tanzania - Mbugua, Mercy; Donovan, Jason A.; Rutsaert, Pieter; Gandhi, Harish; Tamerlane Mark Nas; Templer, Noel A.; de Sousa, Kaue; Mawia, Harriet; Ojiewo, Chris O.; Gichuru, Lilian (CGIAR, 2024)
This brief explores Tanzanian farmers’ requirements for sorghum seed products as input for discussions by CGIAR and NARES on seed product market segmentation and the design of target product profiles (TPPs). We applied a novel approach to identify the requirements—video-based product concept testing (VPCT). Through multiple engagements with breeders, farmers, and industry, we identified seven sorghum seed-product concepts, five targeting the end use—home use, feed and food, industrial malting, food and fodder, forage; one concept on cropping system—intercropping; and one targeting material type—hybrid. We sampled 1,100 farmers from the Dodoma and Shinyanga Regions, where each farmer evaluated and ranked three concepts. Farmers were most likely to have selected the hybrid concept as their most preferred concept, followed by the home use concept. Based on these results, we present a proposal for revisions of the current set of market segments and TPPs for sorghum in Tanzania—one the largest sorghum producer in Eastern Africa.